Rollover and interest rate risks in self-fulfilling debt models - Jo\~ao Ayres; Radoslaw Paluszynski (Inter-American Development Bank (IDB), 2023)
This paper proposes a model of sovereign default that features interest rate multiplicity driven by rollover risk. Our core mechanism shows that the possibility of a rollover crisis by itself can lead to high interest rates, which in turn reinforces the rollover risk. By exploiting complementarity between the traditional notions of slow- and fast-moving crises, our model generates a rich simulated dynamics that features frequent defaults and a volatile bond spread even in the absence of shocks to fundamentals. In the presence of risky income, our mechanism amplifies the dynamics of debt and spreads relative to model benchmarks where equilibrium multiplicity relies on the underlying shocks to income.
Keywords: E44; F34; 330; Sovereign default; Self-fulfilling crises